Exploring Repro-Timing Harm and Benefit - Battisti, Davide (Bioethics, 2026)
It is plausible that time of birth affects one's prospects for wellbeing. Being born during a war or recession might have a negative impact on early life and lifetime wellbeing. In natural reproduction, delaying conception does not result in the same child being born later, but rather a different child altogether; therefore, prospective parents cannot harm/benefit their children by choosing their time of birth. However, we argue that for prospective parents undergoing the IVF process, things are different. Since it is possible to freeze and store embryos indefinitely before implantation, parents can choose their child's time of birth. Because certain birth timings may better support wellbeing, this introduces the possibility of repro-timing harms and benefits. This paper explores this new concept by outlining its theoretical assumptions and examining the moral reasons prospective parents in IVF might have for delaying implantation in the short, medium, and long term.